Monoglyceride lipase mediates tumor-suppressive effects by promoting degradation of X-linked inhibitor of apoptosis protein - Liu, Renyan (Cell Death Differ, 2020)
We have previously reported that Monoglyceride Lipase (MGL) expression is absent or reduced in various human malignancies and MGL-deficient mice develop tumors in multiple organs. Evidence also suggests MGL to be a tumor suppressor, however, the mechanisms underlying its tumor-suppressive actions remain to be investigated. Here, we report a novel function of MGL as a negative regulator of XIAP, an important inhibitor of apoptosis. We found that MGL directly interacted with XIAP and enhanced E3-ligase activity and proteasomal degradation of XIAP. MGL overexpression induced cell death that was coupled with caspase activation and reduced XIAP levels. N-terminus of MGL was found to mediate interactions with XIAP and induce cell death. MGL-deficient cells exhibited elevated XIAP levels and exhibited resistance to anticancer drugs. XIAP expression was significantly elevated in tissues of MGL-deficient animals as well as human lung cancers exhibiting reduced MGL expression. Thus, MGL appears to mediate its tumor-suppressive actions by inhibiting XIAP to induce cell death.